Metal ion sensing functional mono and double-decker lanthanide phthalocyanines: Synthesis, characterization and electrical properties - (:unkn) unknown (ELSEVIER SCIENCE SA, 2010)
We report, in this study, the preparation, physical characterization metal ion sensing properties of peripherally functionalized ionophore ligand, 4,5-bis(6-hydroxyhexylthio)-1,2-dicyanobenzene (1) and its mono 2,3,7,8,12,13,17,18-octakis(6-hydroxyhexylthio)phthalocyaninatometal (II) {M=Zn(II) (2), Cu(II) (3)} and double-decker lanthanide bis-phthalocyanines, {([4,5,4',5' 4 '',5 '',4'''5''']-tetrakis-(6-hydroxyhexylthio)phthalocyanitlatolanthanium(III)}){M[Pc(S-C(6)H(13)OH)(4)](2)} {M=Eu(III) (4), Yb(III) (5), and Lu(III) (6)}. All benzenes on phthalocyanines are functionalized with hydroxyhexylsulfanyl moieties for potential use as soft metal ion binding, such as Ag(+) and Pd(2+). The temperature dependence of the do and ac conduction properties of 4, 5 and 6 thin films have been investigated in the frequency range of 40-10(5) Hz and temperature range 290-436 K. The do results showed an activated conductivity dependence on temperature for all films. Obtained data reveal that ac conductivity obeys the relation sigma(ac)(omega)=A omega(s) and exponent is found to decrease by increasing temperature. The data obtained results were compared with the prediction of the Quantum Mechanical Tunelling (QMT) and Correlated Barrier Hopping (CBH) models. The analysis showed that the CBH model is the dominant conduction mechanism for the electron transport in the films. The new synthesized compounds have been characterized by elemental analysis, FTIR, (1)H and (13)C NMR, MS, UV-vis and EPR spectral data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Double-decker; Aggregation; Ionophore; Impedance spectroscopy; Conductivity; RARE-EARTH COMPLEXES; SUBSTITUTED PHTHALOCYANINES; THIN-FILMS; PART 4; ELECTROCHEMISTRY; SPECTROSCOPY; BINDING; NAPHTHALOCYANINE